2014
DOI: 10.1139/cjfas-2013-0617
|View full text |Cite
|
Sign up to set email alerts
|

Investigating spatial variation and temperature effects on maturity of female winter flounder (Pseudopleuronectes americanus) using generalized additive models

Abstract: Generalized additive models were used to investigate fine-scale spatial variation in female maturity across the three United States' winter flounder (Pseudopleuronectes americanus) stocks. The effect of temperature on maturity was also investigated. Maturity models explicitly incorporating spatial structure performed better than "traditional" methods incorporating spatial effects by aggregating data according to predefined stock boundaries. Models including temperature explained more of the variability in matu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
1
12
0
Order By: Relevance
“…We discovered prominent temporal and spatial patterns in maturity of walleye pollock in Shelikof Strait that may impact both our understanding of the biology and management of the species. There have been only a few attempts to evaluate latitudinal gradients in maturity in gadids [ 34 37 ] or other species [ 2 , 38 40 ], examples of intra-stock spatial variability are rather limited [ 19 , 39 , 41 ]. For instance, both L 50 and length at age of pollock tend to decrease with increasing latitude [ 19 ], consistent with observations of higher growth rates in the southern Bering Sea [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…We discovered prominent temporal and spatial patterns in maturity of walleye pollock in Shelikof Strait that may impact both our understanding of the biology and management of the species. There have been only a few attempts to evaluate latitudinal gradients in maturity in gadids [ 34 37 ] or other species [ 2 , 38 40 ], examples of intra-stock spatial variability are rather limited [ 19 , 39 , 41 ]. For instance, both L 50 and length at age of pollock tend to decrease with increasing latitude [ 19 ], consistent with observations of higher growth rates in the southern Bering Sea [ 42 , 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Given spatial variation in size and age at maturity in fishes, even within a stock (Winton et al. ), obtaining samples from a wide geographic range and in proportion to population densities is recommended. As shown here for Atlantic Herring, perceived variation in maturity can arise due to differential distributions of immature and mature individuals (e.g., as is caused by spawning migrations).…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated the importance of representative sampling of populations for sex and maturity, especially when there is spatial heterogeneity of the population components (e.g., in species with separate juvenile and adult habitats, Gillanders et al 2003;Adams 2017; differential habitat use by sex, Langan et al 2019; or when spawning occurs at specific sites, Lowerre-Barbieri et al 2016). Given spatial variation in size and age at maturity in fishes, even within a stock (Winton et al 2014), obtaining samples from a wide geographic range and in proportion to population densities is recommended. As shown here for Atlantic Herring, perceived variation in maturity can arise due to differential distributions of immature and mature individuals (e.g., as is caused by spawning migrations).…”
Section: Spatial Differences In Maturitymentioning
confidence: 99%
“…Variable removal was conducted one at a time and the reduced model was refit to the data. Candidate univariate and bivariate terms were kept in the model if they contributed to a lower AIC [ 55 ]. The stepwise model selection procedure was repeated until an optimal model was identified according to the above criteria at each stage (i.e.…”
Section: Methodsmentioning
confidence: 99%